Autonomia feminina sobre seus corpos como um Direito Humano : lei de esterilização voluntária n° 9.263/96 - Rocha, Maria Clara Arraes Peixoto (2024)
The purpose of this dissertation transcends the mere legal debate surrounding Law No. 9,263/96 (Family Planning Law). It aims to examine the circumstances and contexts that involve such a normative, adopting a perspective that deviates from the traditional technicist and technocratic argumentation of Law. It is imperative to understand that Human Rights are fundamentally a political issue, rather than strictly a legal one. In this sense, this research aims to investigate the social and legal factors surrounding the referred law and its policies related to the performance of tubal ligation surgery on women who do not desire gestational motherhood and opt for this contraceptive method. More specifically, the study focuses on the prerequisites established in art. 10, inc. I, and its § 5°, which defined the conditions under which the contraceptive practice of sterilization surgery was permitted until its amendment by the new Law No. 14,443, of 2022. The analysis concentrates on cisgender women, aiming to deepen the understanding of the impacts and implications of this legislation on their lives and reproductive rights. The main theoretical foundation utilized includes contributions on compulsory motherhood (ZEIFERT, 2019), legal feminism (DA SILVA, 2019), biopower (FOUCAULT, 2018), and institutional racism (WERNECK, 2019). Historical and legal-dogmatic methods were applied, as well as documental bibliographic research. The first method was used to analyze the political context and to understand the social and legal influences; the second, to conduct a critical analysis of the legal system itself, of positive law, and to make connections with gender discussions related to women's self-sufficiency in deciding about their own bodies. Furthermore, an investigative manifestation of the complaint is proposed, pointing out cases of compulsory sterilization against black women as a form of bodily mutilation ensured by institutional racism through eugenic discourses of the Brazilian Judiciary, and making connections with gender discussions related to women's self-sufficiency over their bodies, to provide a better depth of the hypotheses on the subject. Two cases of compulsory sterilization were briefly analyzed as a means of institutional racism via eugenic discourses. The relevance of this theme aligns with the reflection on bodily autonomy in the face of the institutions of Law, family, and marriage, as in practice, women have had their Reproductive Human Rights denied daily by the Brazilian legal system represented by Law No. 9,263/96. The results of this study evidenced that there are several legal unconstitutionality issues posed by the aforementioned old law, and that the legal modus operandi not only infringed constitutional principles of its own government but also international agreements to which Brazil committed to comply with decisions regarding Women's Reproductive Rights, without affronting the freedom and dignity of women's human persons.